A dual origin for water in carbonaceous asteroids revealed by CM chondrites. (April 2018) - Piani, Laurette; Yurimoto, Hisayoshi; Remusat, Laurent
Abstract Carbonaceous asteroids represent the principal source of water in the inner Solar System and might correspond to the main contributors for the delivery of water to Earth. Hydrogen isotopes in water-bearing primitive meteorites, for example carbonaceous chondrites, constitute a unique tool for deciphering the sources of water reservoirs at the time of asteroid formation. However, fine-scale isotopic measurements are required to unravel the effects of parent-body processes on the pre-accretion isotopic distributions. Here, we report in situ micrometre-scale analyses of hydrogen isotopes in six CM-type carbonaceous chondrites, revealing a dominant deuterium-poor water component (δD = −350 ± 40‰) mixed with deuterium-rich organic matter. We suggest that this deuterium-poor water corresponds to a ubiquitous water reservoir in the inner protoplanetary disk. A deuterium-rich water signature has been preserved in the least altered part of the Paris chondrite (δDParis ≥ −69 ± 163‰) in hydrated phases possibly present in the CM rock before alteration. The presence of the deuterium-enriched water signature in Paris might indicate that transfers of ice from the outer to the inner Solar System were significant within the first million years of the history of the Solar System. Laboratory analyses on six carbonaceous chondrites suggest the presence of two water sources with different deuterium (D) enrichment levels in the protoplanetary disk: a D-poor inner reservoir and a D-rich water component transferred inward from the outer disk.